Towards illiberal conditioning? New politics of media regulations in Poland (2015–2018). Issue 1 (2nd January 2020) - Surowiec, Paweł; Kania-Lundholm, Magdalena; Winiarska-Brodowska, Małgorzata
ABSTRACT: In this article, we examine how media policy changes aid de-democratisation in Poland. Unfolding the logic underpinning the new politics of media regulations, this article argues that media policy paints a nuanced picture of democratic backsliding. Our Foucault-inspired discourse analysis of media policy archive focuses on the rise of illiberal trends at the cross-roads of the Polish hybrid media system, democracy and society. We find these trends display the features of centralisation of power, cultural politics, political partisanship and social polarisations. We explain these notions, using the concepts of "executive aggrandisement" and "politicisation" of public service media sector.